Finite element analysis of blind bolted flush end-plate connection on square hollow section using ANSYS [electronic resource] - Chong, Shin Yee, 1989- (2013)
Project Paper (Sarjana Muda (Awam - Struktur)) - Universiti Teknologi Malaysia, 2013